PENINGKATAN HASIL BELAJAR SIFAT-SIFAT BANGUN DATAR DENGAN MODEL KOOPERATIFE TIPE GI DI SD - Aliatri, Aliatri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This study comes from the reality on the ground is at SDN 18 Sungai Aur that teachers use Cooperative Model Study Group Investigation (GI) so that the students are learning hard to understand the material properties of a flat wake, resulting in decreased student learning outcomes. Seeing the above phenomenon researchers interested in applying Cooperative Model Study Group Investigation (GI) to improve student learning outcomes in the classroom V SD. Research purposes to describe the plan, execution, and learning outcomes wake properties flat with Cooperative Model Study Group Investigation (GI) in class V SDN 18 Sungai Aur District Pasaman Barat. This research is action research, qualitative and quantitative research. consists of planning, implementation, observation, reflection. The subjects were teachers and fourth grade students of SDN 18 Sunagi Aur District Pasaman Barat. The results showed Cooperative Study Group Investigation (GI) can improve student learning outcomes. The first planning meeting of the first cycle of 50% less criteria, implementation of aspects of teachers 59% less criteria and aspects of students' criteria 59% less, then continued in the first cycle II planning meeting 67% of the criteria sufficiently, the implementation of aspects of the 71% criterion of good teachers, and aspects of the students 62% criterion enough, then continued on the second cycle of planning aspect is very good 92% criteria, the implementation of aspects of teachers 93% criterion very well, and aspects of students 90% criterion very well, has been an increase from the first cycle of meetings I and II to second cycle. It can be concluded by using Cooperative Study Group Investigation (GI) improved learning outcomes. Kata kunci: peningkatan; hasil; belajar; model; kooperatif; gi.